2021
DOI: 10.1021/acs.accounts.1c00326
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adaptable Tropos Catalysts

Abstract: Conspectus Biological systems have often served as inspiration for the design of synthetic catalysts. The lock and key analogy put forward by Emil Fischer in 1894 to explain the high substrate specificity of enzymes has been used as a general guiding principle aimed at enhancing the selectivity of chemical processes by optimizing attractive and repulsive interactions in molecular recognition events. However, although a perfect fit of a substrate to a catalytic site may enhance the selectivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Subsequently, catalytic asymmetric construction of cyclopentene 15 through an asymmetric allylic alkylation (AAA) reaction was investigated. Although the AAA reaction has been widely used as a key step in the total synthesis of natural products, it remains a major challenge for the reaction involving cyclic allyl alcohol-derived substrates. In particular, Hamada found that the enantiomeric excess (ee) value was only 50% for the reaction of 2-methyl-2-cyclopentenyl carbonate ( 17 ) with dimethyl malonate . To the best of our knowledge, no reports have addressed the allylic substitution reactions of 2-substituted 2-cycloalkenyl carbonates (such as 17 ) with malonate derivatives (such as 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, catalytic asymmetric construction of cyclopentene 15 through an asymmetric allylic alkylation (AAA) reaction was investigated. Although the AAA reaction has been widely used as a key step in the total synthesis of natural products, it remains a major challenge for the reaction involving cyclic allyl alcohol-derived substrates. In particular, Hamada found that the enantiomeric excess (ee) value was only 50% for the reaction of 2-methyl-2-cyclopentenyl carbonate ( 17 ) with dimethyl malonate . To the best of our knowledge, no reports have addressed the allylic substitution reactions of 2-substituted 2-cycloalkenyl carbonates (such as 17 ) with malonate derivatives (such as 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these catalysts often provide an “anchor-like” immobilization where only one ligand is connected to the support, which usually distorts the coordination environment of Rh sites and thus affects the reactivity and reproducibility. , Furthermore, most of the supports used in the heterogenization process are rigid materials such as silica, in which three-dimensional active sites hardly adapt their molecular structures to a reacting substrate through noncovalent interaction, thereby limiting catalytic performances of heterogenized dirhodium catalysts . Therefore, the development of a facile way to obtain heterogenized dirhodium carboxylates in a flexible but nonstationary microenvironment with self-adaptive catalytic behaviors is urgently needed. …”
Section: Introductionmentioning
confidence: 99%
“…Such a system represents a cofactor ligand, which is stereoselectively aligned upon interaction with a chiral anionic auxiliary. 48,49 It has been successfully demonstrated by Suginome and coworkers that dynamic helical polymer-based catalysts show nonlinear effects in asymmetric catalysis, their enantioselectivity can be switched, and the catalytic activity can be turned on or off. 50,51 We developed a different strategy using stereodynamically flexible biphenyls as the ligand core of the targeted catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%